Organisation behaviour and design - Cushway, Barry (London : Kogan page, 1993)
Explains in practical terms how organizations are constructed, and how the behaviour of individuals and groups affect this structure. Along with descriptions of organizational behavioural concepts, the text includes questionnaires which enable readers to assess their own organizational skills.
Includes index
eng
Keywords: Organizational behavior